Hubungan Sunnah Rasullullah S.A.W. Dalam Amalan Berkongsi Makanan Menggunakan Dulang Dengan Tahap Kekenyangan - Ibrahim, Abu Bakar; Noor Azah, Hashim; Hanie Nadirah, Mohd Tamrin; Rashidi, Abbas (2017)
Sharing of food in tray is Sunnah of Prophet Muhammad s.a.w. The purpose of this study is to determine the relationship between methods of sharing food in tray with satiety. Groups of 108 and 120 respondents were stratified randomly chosen respectively according to sex and age from dedicated population. The level of satiety was measured using 1-5 Likert scale and all data were statistically analysed using Statistical Package for Social Science (SPSS) version 21. The results show negative relationship at medium strength (r=0.37) between the level of satiety with the number of people who share the food in tray and positive relationship at low strength (r=0.28) between the level of satiety with the number of food portion. Food with 4 portions size enough to share by 6 peoples where they feel moderate full.